KAJIAN DEBIT AIR SUB-SUB DAS RIAM KIWA SUB DAS MARTAPURA KABUPATEN BANJAR PROVINSI KALIMANTAN SELATAN - Muhammad Nasih; Eko Rini Indrayatie; Syarifuddin Kadir (Jurnal Sylva Scienteae, 2020)
This research aims to know the condition of sub-sub Riam Kiwa watershed sub watershed Martapura include the closure of land, slopes and critical land and to know water discharge of sub-sub Riam Kiwa watershed sub Martapura watershed, the methods used in this research is analysis of GIS data and measurements of water discharge. Data show that forest cover experienced a very large decline on 2012 in the amount of 20,96 % to 18,536 % on 2017, that has impact on decreased of water discharge. The results of 2009 and 2013’s critical land data shows that critical area on the wane so it could be said that from 2009 to 2013 water system balance is getting better and getting better as a media production to cultivate land cover vegetation relic sub-sub watershed Riam Kiwa sub Martapura watershed. Data on the condition of increasing forest cover area, secondary dry land, and plantation forest in the slope class are rather steep (15-25 %) and steep (25-40 %), so that can slow run off water. Water discharge measurement results performed on the upper reaches in sub-sub watershed Riam Kiwa sub Martapura watershed minimum water discharge was 11, 26 m³/s and the maximum water discharge was 98.61 m³/s in which the obtained average discharge the river water as much as 50.96 m³/s. Water discharge measurement results performed on the lower in sub-sub watershed Riam Kiwa sub Martapura watershed minimum water discharge is 23, 61 m³/s and the maximum water discharge was 143.16 m³/second which obtained an average of the water discharge of the River as much as 82.24 m³/sKeywords: Water Discharge, Land, the closure of critical land, slopes